A Novel Function of the MA-3 Domains in Transformation and Translation Suppressor Pdcd4 Is Essential for Its Binding to Eukaryotic Translation Initiation Factor 4A - Yang, Hsin-Sheng (American Society for Microbiology, 2004)
Αn α-helical MA-3 domain appears in several translation initiation factors, including human eukaryotic translation initiation factor 4G (eIF4G) and DAP-5/NAT1/p97, as well as in the tumor suppressor Pdcd4. The function of the MA-3 domain is, however, unknown. C-terminal eIF4G (eIG4Gc) contains an MA-3 domain that is located within the eIF4A-binding region, suggesting a role for eIF4A binding. Interestingly, C-terminal DAP-5/NAT1/p97 contains an MA-3 domain, but it does not bind to eIF4A. Mutation of amino acid residues conserved between Pdcd4 and eIF4Gc but not in DAP-5/NAT1/p97 to the amino acid residues found in the DAP-5/NAT1/p97 indicates that some of these amino acid residues within the MA-3 domain are critical for eIF4A-binding activity. Six Pdcd4 mutants (Pdcd4(E249K), Pdcd4(D253A), Pdcd4(D414K), Pdcd4(D418A), Pdcd4(E249K,D414K), and Pdcd4(D253A,D418A)) lost >90% eIF4A-binding activity. Mutation of the corresponding amino acid residues in the eIF4Gc also produced similar results, as seen for Pdcd4. These results demonstrate that the MA-3 domain is important for eIF4A binding and explain the ability of Pdcd4 or eIF4Gc but not DAP-5/NAT1/p97 to bind to eIF4A. Competition experiments indicate that Pdcd4 prevents ca. 60 to 70% of eIF4A binding to eIF4Gc at a Pdcd4/eIF4A ratio of 1:1, but mutants Pdcd4(D253A) and Pdcd4(D253A,D418A) do not. Translation of stem-loop structured mRNA is susceptible to inhibition by wild-type Pdcd4 but not by Pdcd4(D253A), Pdcd4(D418A), or Pdcd4(D235A,D418A). Together, these results indicate that not only binding to eIF4A but also prevention of eIF4A binding to the MA-3 domain of eIF4Gc contributes to the mechanism by which Pdcd4 inhibits translation.